Expression of Concern: Refat et al. Antioxidant, Antigenotoxic, and Hepatic Ameliorative Effects of Quercetin/Zinc Complex on Cadmium-Induced Hepatotoxicity and Alterations in Hepatic Tissue Structure. Coatings 2021, 11, 501 - Coatings Editorial Office, Coatings Editorial Office (Coatings (Basel), 2024)
With this notice, the Editorial Office of Coatings states its awareness of the concerns relating to both the authorship and research integrity of the published paper “Antioxidant, Antigenotoxic, and Hepatic Ameliorative Effects of Quercetin/Zinc Complex on Cadmium-Induced Hepatotoxicity and Alterations in Hepatic Tissue Structure” [...]